Ready or not? Psychologists’ perceptions of work readiness in the age of AI - McDonald, Curtis; Schweinsberg, Ashleigh (Frontiers in Computer Science, 2025)
The Fourth Industrial Revolution, driven by rapid AI advancements, presents significant challenges and opportunities for psychologists. As these dynamics evolve, it is crucial to prepare practitioners adequately, yet current accreditation frameworks seem insufficient. This qualitative study explored work readiness (WR) perceptions among fully registered psychologists in Australia within this shifting technological landscape. Semi-structured interviews with six participants, analysed using reflexive thematic analysis and a social constructionist approach, revealed three themes: (1) Human-Centric WR Skills Are Irreplaceable by AI, (2) AI Will Enhance Psychological Practice, and (3) Education Must Adapt to Emphasise AI-Integration and Human-Centric Qualities. The study identifies a critical gap between current accreditation, which often prioritises technical skills, and the humanistic capacities valued by psychologists. These findings advocate for a re-evaluation of psychology’s accreditation pathway, promoting a more holistic approach to preparing future psychologists for an AI-integrated profession. This research contributes foundational insights to the discourse on WR in psychology, emphasising the balance between technological proficiency and essential human skills in navigating AI integration. It also encourages dialogue between accreditation bodies and psychologists to reconcile differing WR perspectives and ensure the future preparedness of practitioners.